A study to determine Calorie and protein intake in adolescent school girls of Indore city, M.P., India - Sunita Solanki; Mahendra Solanki (International Journal of Medical Research and Review, 2022)
Introduction: Adolescence is a significant period of human growth and maturation. This period ofrapid growth requires a well-balanced diet. An inadequate diet and unfavourable environmentadversely influence the growth resulting in short stature and low lean body mass. Not muchattention has been paid to adolescents by nutrition-related programmes. Hence, this study wasplanned to assess the dietary intake of adolescent girls. Method: This was a cross-sectional studyconducted in five schools in urban areas of Indore city. The study group included 400 school girls ofage 11 to 18 years. After taking written informed consent from the parents, data was collected onpersonal information, dietary intake and socioeconomic status. Anthropometric measurements weredone, and data were analyzed. Results: The calorie intake in this study ranged from 69% to 86% ofR.D.A. Mean protein intake ranged from 71.5% to 73.7% of R.D.A., and mean iron intake rangedfrom 50% to 71.4% R.D.A. All the girls were consuming an inadequate amount of calories, proteinsand iron. Conclusion: All the adolescent girls in this study had low intakes of calories, iron andprotein, which is comparable to that found in other Indian studies.